Structural basis for abrogated binding between staphylococcal enterotoxin A superantigen vaccine and MHC-IIα - Krupka, Heike I. (Cold Spring Harbor Laboratory Press, 2002)
Staphylococcal enterotoxins (SEs) are superantigenic protein toxins responsible for a number of life-threatening diseases. The X-ray structure of a staphylococcal enterotoxin A (SEA) triple-mutant (L48R, D70R, and Y92A) vaccine reveals a cascade of structural rearrangements located in three loop regions essential for binding the α subunit of major histocompatibility complex class II (MHC-II) molecules. A comparison of hypothetical model complexes between SEA and the SEA triple mutant with MHC-II HLA-DR1 clearly shows disruption of key ionic and hydrophobic interactions necessary for forming the complex. Extensive dislocation of the disulfide loop in particular interferes with MHC-IIα binding. The triple-mutant structure provides new insights into the loss of superantigenicity and toxicity of an engineered superantigen and provides a basis for further design of enterotoxin vaccines.